Struct set of didactic activities for introductory programming teaching (Research, Society and Development, 2022)
This work was carried out within the scope of the Educational Design Research (EDR) methodology, which seeks to provide solutions to problems experienced in teaching practice. The research developed has the purpose of creating, developing, implementing and evaluating a teaching methodology based on a set of didactic activities (DAs) focused on providing students who take the introductory programming subject in the technical course in computer science integrated with high school, pace of study and qualified feedback. The DAs were developed to carry out a continuous monitoring of student performance so that the high rate of dropout and failure are reduced. During this methodological process, the teacher is able to identify the gaps presented by the students and carry out the resumption of the content individually and/or in groups, preventing that the accumulation of doubts being an obstacle to learning. Feedback to students was carried out taking into account reading comprehension, mathematical notions, logical reasoning and abstraction, which represent the four essential pillars to be evaluated in programming teaching. The results obtained indicate that the DAs developed are of great worth in the construction of students' knowledge, observing satisfactory performances and, consequently, contributing to decrease the failure of the Course.